Digital Game-Based Learning Effectiveness in Formal Education: A Review - I Kadek Budi Sandika; I Nyoman Yoga Trisemarawima; Anggie Birda Ardelia Ghani (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The 21st-century technological landscape has significantly transformed conventional education through the adoption of Digital Game-Based Learning (DGBL) and gamification. This study aims to conduct a systematic literature review using the PRISMA protocol to map publication trends, pedagogical effectiveness, ideal game mechanics, and research disparities across one hundred peer-reviewed journal articles published between 2014 and 2026. The findings reveal an exponential growth in publication volume, heavily dominated by contributions from Asia, Europe, and North America. Integrating core game elements such as points, leaderboards, badges, challenges, and narrative framing empirically enhances intrinsic motivation, long-term memory retention, and cognitive learning outcomes. Furthermore, this review identifies a noticeable research divide: computer science journals prioritize technical architectures and adaptive algorithms, whereas educational journals focus on psychopedagogical validation. Practical implications highlight the urgent need for interdisciplinary collaboration, teacher digital literacy programs, and equitable ICT infrastructure to support inclusive digital curricula.